Plant Growth Variation At Combined Progeny And Provenance Of 5-Year-Old Intsia Bijuga (Colebr. )O.Kuntze In Sobang, Banten - Hamdan Adma Adinugraha; Sugeng Pudjiono; Burhan Ismail; Mahfudz Mahfudz (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2014)
This study was conducted to evaluate plant growth of Intsia bijuga at 5 years old in Sobang, Banten for supplying good genetic material in the future. Establishment of the trial was conducted in 2007 using Randomized Complete Block Design (RCBD) that consisted of 6 blocks, 100 families nested in 10 provenances, 4 treeplot for each family with a spacing of 4 x4 m. Measurements were taken periodically every year on the survival percentage, total height and stem diameter at the breast height or dbh. At the age of 5 years showed that the significant differences among provenance in survival percentage that ranged from 41.61 to 65.11 %, average of plant height were 1.04 to 2.82 m and dbh 1.24 to 1.59 cm. The growth variation families also showed significant differences in height and diameter. The survival rate ranged from 12.5-91.67 %, average plant height were 0.52-2.55 m and dbh 0.90-2.44 cm. Individual tree heritability estimate for height was height (0.344) while that of diameter was moderate (0.259). Family heritabilities for height and diameter was considered moderate, namely 0.573 and 0.491 respectively. Genetic correlation between height and diameter growth was positive and high (0.834).